DIGITAL PUBLIC SERVICES AND CITIZEN TRUST IN GOVERNMENT - Ahmad Rosikhul Fahmi (Alqaprint Jatinangor, 2025)
This study explores the relationship between digital public services and citizen trust in government through an extensive literature review approach. As governments worldwide embrace digital transformation, understanding how digitalization influences public trust has become a central theme in governance studies. The review synthesizes findings from peer-reviewed articles published in major academic databases, emphasizing transparency, accessibility, responsiveness, and data security as critical determinants of citizen trust. It reveals that well-designed digital platforms enhance trust by promoting efficiency and participatory governance, while poorly implemented systems may deepen scepticism and digital inequality. The analysis further identifies contextual variations across regions, highlighting that cultural, institutional, and technological readiness shape citizens’ perceptions of governmental reliability. Methodologically, this research employs thematic analysis to classify and interpret key trends in prior studies. The findings contribute to theoretical discussions on e-governance, social capital, and institutional legitimacy. Ultimately, this paper underscores the strategic importance of digital governance in reinforcing democratic accountability and sustaining long-term citizen confidence.